Measurement and evaluation of low-carbon tourism development on islands: A case study in Changdao, China - Mengsha Wang; Jiayu Zuo (PLoS ONE, 2025)
China’s island tourism is still in the exploratory stage, and the carbon emissions due to island tourism development are still prominent. This study assesses the development of low-carbon tourism on Changdao Island in China. We constructed an evaluation model for low-carbon tourism on islands based on the driver-pressure-state-impact-response model, and the Entropy Weight Method-Analytical Hierarchy Process Method was combined with the weighting method to determine the index weights of ench evaluation-indicator. The annual changes in the development level of low-carbon tourism, the weights of the indicators, the characteristics of the scores, the low-carbon development mode, and key factors of island tourism were analyzed. The results of the study showed that the indicator “impact” was the most influential element of the island’s low-carbon tourism, and the ecological environment value was higher than that of the economic value. Moreover, energy saving and consumption reduction helped tourists to have a better experience, which further enabled island tourism to have a larger market size. The “response” also occupied a crucial position, where the weighted value of government planning was twice as high as that of corporate practice. The other elements were “pressure”, “state”, and “driving forces”, which showed that low carbon emissions are an important criterion for the island tourism environment and economic factors have the greatest effect in terms of the “driving forces”. The study evaluated the level of low-carbon development in island regionals across multiple dimensions, filled the literature gap, and provided a reference for the study of regional low-carbon and sustainable development of tourism.